(a+b)3 = a3 + 3a2b +3ab2 + b3 - (a+b)3 = - (a3 + 3a2b +3ab2 + b3) therefore, (-a-b)3 = -a3 - 3a2b - 3ab2 - b3 -bro.....hop tizz helps bt try nt 2 rest ur brain Posted by sharan.kumaran....(student)on 16/9/11

(a+b)3 = a3 + 3a2b +3ab2 + b3 - (a+b)3 = - (a3 + 3a2b +3ab2 + b3) therefore, (-a-b)3 = -a3 - 3a2b - 3ab2 - b3 -bro.....hop tizz helps bt try nt 2 rest ur brain Posted by sharan.kumaran....(student)on 16/9/11

(a+b)3 = a3 + 3a2b +3ab2 + b3 - (a+b)3 = - (a3 + 3a2b +3ab2 + b3) therefore, (-a-b)3 = -a3 - 3a2b - 3ab2 - b3 -bro.....hop tizz helps bt try nt 2 rest ur brain Posted by sharan.kumaran....(student)on 16/9/11

(a-b)^{3 }= (a-b) (a-b)^{2} =(a-b) ( a^{2 }+ b^{2} -2ab) = a(a^{2} + b^{2} - 2ab) -b (a^{2} +b^{2} -2ab) = Posted by Moonisha(student)on 19/8/12

(a-b)^{3 }= (a-b) (a-b)^{2} =(a-b) ( a^{2 }+ b^{2} -2ab) = a(a^{2} + b^{2} - 2ab) -b (a^{2} +b^{2} -2ab) = Posted by Moonisha(student)on 19/8/12

(a-b)^{3 }= (a-b) (a-b)^{2} =(a-b) ( a^{2 }+ b^{2} -2ab) = a(a^{2} + b^{2} - 2ab) -b (a^{2} +b^{2} -2ab) = Posted by Moonisha(student)on 19/8/12

(a-b)^{3 } = (a)^{3}+ (-b)^{3}-3*a*b*(a-b) = a^{3} -b^{3} -3a^{2}b +3ab^{2} Posted by V Sukram(parent)on 22/12/12

(a-b)^{3 } = (a)^{3}+ (-b)^{3}-3*a*b*(a-b) = a^{3} -b^{3} -3a^{2}b +3ab^{2} Posted by V Sukram(parent)on 22/12/12

(a-b)^{3 } = (a)^{3}+ (-b)^{3}-3*a*b*(a-b) = a^{3} -b^{3} -3a^{2}b +3ab^{2} Posted by V Sukram(parent)on 22/12/12

Posted by ramandeep.singh(MeritNation Expert)on 21/1/13 This conversation is already closed by Expert

Posted by ramandeep.singh(MeritNation Expert)on 21/1/13 This conversation is already closed by Expert

Posted by ramandeep.singh(MeritNation Expert)on 21/1/13 This conversation is already closed by Expert